Combining Hepatitis B Virus RNA and Hepatitis B Core–Related Antigen: Guidance for Safely Stopping Nucleos(t)ide Analogues in Hepatitis B e Antigen–Positive Patients With Chronic Hepatitis B. (25th March 2020) - Fan, Rong; Peng, Jie; Xie, Qing; Tan, Deming; Xu, Min; Niu, Junqi; Wang, Hao; Ren, Hong; Chen, Xinyue; Wang, Maorong; Sheng, Jifang; Tang, Hong; et al.
Abstract: Background: Safe nucleos(t)ide analogue discontinuation in chronic hepatitis B (CHB) is an unmet need. We aimed to investigate whether combining hepatitis B virus (HBV) RNA and hepatitis B core–related antigen (HBcrAg) could perform satisfactorily in predicting off-treatment outcomes. Methods: The evaluation cohort included 127 hepatitis B e antigen (HBeAg)–positive patients from a multicenter prospective trial who stopped telbivudine-based therapy after achieving HBeAg seroconversion and HBV DNA < 50 IU/mL for > 48 weeks. As validation, 59 patients treated with entecavir or tenofovir before discontinuation were analyzed. Results: At the end of treatment (EOT), HBV RNA and HBcrAg were significant independent predictors of the clinical relapse risk. In the evaluation cohort, no clinical relapse occurred among patients with negative HBV RNA and HBcrAg < 4 log10 U/mL at EOT (low-risk group), whereas 46.8% patients with positive HBV RNA and HBcrAg ≥ 4 log10 U/mL (high-risk group) experienced clinical relapse during 4-year posttreatment follow-up ( P  < .001); the corresponding incidences in the validation cohort were 0% and 69.4% ( P  < .001), respectively. More patients in the low-risk group achieved HBsAg loss than the other patients after treatment cessation (16.1% vs 1.3%, P  = .002). Conclusions: Combining HBV RNA and HBcrAg performed satisfactorily in predicting clinical relapse and HBsAg loss after treatment cessation in HBeAg-positive patients with CHB. The combination of hepatitis B virus RNA and hepatitis B core–related antigen performed satisfactorily in predicting clinical relapse and hepatitis B surface antigen loss after stopping nucleos(t)ide analogue treatment among noncirrhotic hepatitis B e antigen–positive patients with chronic hepatitis B and could be used to guide safe discontinuation. Abstract : The combination of hepatitis B virus RNA and hepatitis B core–related antigen performed satisfactorily in predicting clinical relapse and hepatitis B surface antigen loss after stopping nucleos(t)ide analogue treatment among noncirrhotic hepatitis B e antigen–positive patients with chronic hepatitis B, and could be used to guide safe discontinuation in clinical practice.